1983
DOI: 10.1021/bi00285a036
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of papain-solubilized human histocompatibility antigen HLA-B40 (-Bw60). An outline of alloantigenic determinants

Abstract: The primary structure of papain-solubilized human histocompatibility antigen HLA-B40 (-Bw60) has been determined. Its comparison with that of the cross-reactive HLA-B7 antigen allows for the first time a direct sequence comparison between two HLA-B locus products and an outline of the location of their alloantigenic sites. Overall sequence homology between HLA-B40 and HLA-B7 is 93%. Of 19 detected differences, 18 are located in the two amino-terminal domains (residues 1-182). Half of them are clustered in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Thus, since positions that differ from HLA-A and -B also vary between alleles of a single locus, the limited sequences available have not been useful in identifying residues unique to HLA-A or -B alleles (9,10). Monoclonal antibodies reacting with the protein products of only one allele of each locus have been isolated (e.g., ref.…”
mentioning
confidence: 99%
“…Thus, since positions that differ from HLA-A and -B also vary between alleles of a single locus, the limited sequences available have not been useful in identifying residues unique to HLA-A or -B alleles (9,10). Monoclonal antibodies reacting with the protein products of only one allele of each locus have been isolated (e.g., ref.…”
mentioning
confidence: 99%
“…However, it is difficult to assess the relevance of such an amino acid substitution in view of the observation that a free cysteine occupies, for example, a similarly polymorphic site in the HLA-Cw3 sequence (position 9). In contrast, the appearance of a serine in position 131 is likely to have a more profound effect on the conformation of HLA-B27, because this nonconservative replacement occurs at a site invariably occupied by a species-associated arginine residue in human and lysine in mice (22). The species specificity of this residue is confirmed in all murine class I gene sequences so far known, which include H-2Kq, H-2Kwa (see ref.…”
Section: Resultsmentioning
confidence: 92%
“…4). The occupied by a potentially reactive cysteine that might influence the intermolecular interactions of HLA-B27 due to its location in an area thought to mediate the binding of monoclonal antibodies as well as of alloantibodies (22). However, it is difficult to assess the relevance of such an amino acid substitution in view of the observation that a free cysteine occupies, for example, a similarly polymorphic site in the HLA-Cw3 sequence (position 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported the production and characterization of an antibody to one of the most hydrophilic peptide regions of HLA-B7 antigen (7). These studies demonstrated that this region of the antigen did not encode for an allorecognition site and the conformation of this region was highly dependent upon the presence of bound A2-microglobulin.We report here on the characteristics of an antiserum produced to a synthetic peptide corresponding to residues 61-83 of the HLA-B7 antigen heavy chain amino acid sequence, which represents a region of high structural variability when compared to other class I antigen amino acid sequences (1,8,9). …”
mentioning
confidence: 99%